2012
DOI: 10.1016/j.wear.2012.01.016
|View full text |Cite
|
Sign up to set email alerts
|

A pin-on-disc study of the rate of airborne wear particle emissions from railway braking materials

Abstract: The current study investigates the characteristics of particles generated from the wear of braking materials, and provides an applicable index for measuring and comparing wear particle emissions. A pin-on-disc tribometer equipped with particle measurement instruments was used. The number concentration, size, morphology, and mass concentration of generated particles were investigated and reported for particles 10 nm to 32 µm in diameter. The particles were also collected on filters and investigated using EDS an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 15 publications
2
41
0
Order By: Relevance
“…It is suggested that differences between the dominant wear mechanisms cause the differences in wear particle shape (Stachowiak et al, 2008). This suggestion was confirmed by Abbasi et al (2012b) in a laboratory study of airborne wear particles. Figure 2 shows an image of particles from diesel exhaust.…”
Section: Particle Morphologymentioning
confidence: 76%
See 3 more Smart Citations
“…It is suggested that differences between the dominant wear mechanisms cause the differences in wear particle shape (Stachowiak et al, 2008). This suggestion was confirmed by Abbasi et al (2012b) in a laboratory study of airborne wear particles. Figure 2 shows an image of particles from diesel exhaust.…”
Section: Particle Morphologymentioning
confidence: 76%
“…Abbasi et al (2012b) suggested a method for measuring the airborne wear particle emission rate (AWPER) from wheel-rail contacts and braking materials. This method can be used by manufacturers to demonstrate the competitive advantage of their products.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, reduced wear and prolonged life of brake pads and discs also produce benefits in terms of pollution since the wear produce solid particles and contaminants whose impact on the surrounding environment is still the matter of monitoring and research [1][2] [3].…”
Section: Introductionmentioning
confidence: 99%